2021
DOI: 10.1111/twec.13088
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric cultural proximity and greenfield foreign direct investment

Abstract: The Robert Schuman Centre for Advanced Studies (RSCAS), created in 1992 and directed by Professor Brigid Laffan, aims to develop inter-disciplinary and comparative research and to promote work on the major issues facing the process of integration and European society. The Centre is home to a large post-doctoral programme and hosts major research programmes and projects, and a range of working groups and ad hoc initiatives. The research agenda is organised around a set of core themes and is continuously evolvin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 60 publications
(128 reference statements)
1
12
0
Order By: Relevance
“…As highlighted by Shenkar (2001), Tung and Verbeke (2010) and Li et al (2017) cultural relationships, which are relevant in the context of international economic exchanges, are far from being symmetric. Furthermore, Fiorini et al (2021) and Felbermayr and Toubal (2010) found evidence of cultural asymmetry between country pairs. Their evidence points to an important role in the asymmetric dimension of cultural affinity in determining cross-country socioeconomic interactions and calls for a broader notion of cultural proximity capable of reflecting asymmetric affinity between two countries.…”
Section: Symmetrymentioning
confidence: 96%
See 3 more Smart Citations
“…As highlighted by Shenkar (2001), Tung and Verbeke (2010) and Li et al (2017) cultural relationships, which are relevant in the context of international economic exchanges, are far from being symmetric. Furthermore, Fiorini et al (2021) and Felbermayr and Toubal (2010) found evidence of cultural asymmetry between country pairs. Their evidence points to an important role in the asymmetric dimension of cultural affinity in determining cross-country socioeconomic interactions and calls for a broader notion of cultural proximity capable of reflecting asymmetric affinity between two countries.…”
Section: Symmetrymentioning
confidence: 96%
“…To stress this argument even further, in reviewing the literature on gravity models for international migration, explicitly stated that cultural proximity is one of the most important "time invariant" dyadic components of bilateral migration costs. This definition of cultural proximity limits the capacity to capture all of the important dimensions of cultural affinity which have already been questioned in the international business, anthropological, sociological and economics literature (see Shenkar, 2001;Li et al 2017;Felbermayr & Toubal, 2010;Giuliano & Nunn, 2020;Fiorini et al 2021;Tung Verbeke, 2010). In this regard, Felbermayr and Toubal (2010).…”
Section: Related Literaturementioning
confidence: 99%
See 2 more Smart Citations
“…The economics literature has looked at a similar construct, cultural proximity, which has been found to influence trade (Felbermayr & Toubal, 2010) and foreign direct investment flows (Fiorini et al, 2021). Wang et al (2014) assert that it is easier for firms to engage in business with culturally close partners because of reduced uncertainty, which, in turn, makes it easier to share knowledge.…”
Section: Perceived Institutional Familiaritymentioning
confidence: 99%